Examples

Example 1

Example 2

Example 3

Example 4 Important You are here

Example 5

Example 6 Important

Example 7

Example 8

Example 9

Example 10 Important

Example 11 Important

Example 12

Example 13 Important

Example 14 Important

Example 15

Example 16 Important

Example 17

Example 18 Important

Example 19 Important

Last updated at Aug. 2, 2021 by Teachoo

Example 4 Check graphically, whether the pair of equations x + 3y = 6 and 2x – 3y= 12 is consistent. If so, solve them graphically. Let equations be x + 3y = 6 2x – 3y = 12 Let’s draw their graphs For Equation (1) x + 3y = 6 Putting x = 0 0 + 3y = 6 3y = 6 y = 6/3 y = 2 So, x = 0, y = 2 is a solution i.e. (0, 2) is a solution Putting y = 0 x + 3(0) = 6 x + 0 = 6 x = 6 So, x = 6, y = 0 is a solution i.e. (6, 0) is a solution For Equation (2) 2x − 3y = 12 Putting x = 0 2(0) − 3y = 12 0 − 3y = 12 −3y = 12 y = 12/(−3) y = −4 So, x = 0, y = −4 is a solution i.e. (0, −4) is a solution Putting y = 0 2x − 3(0) = 12 2x = 12 x = 12/2 x = 6 So, x = 6, y = 0 is a solution i.e. (6, 0) is a solution We will plot both equations on the graph Since the lines intersect, the given equations are consistent And solution is (6, 0)